Stomata of Grass in The Ex Tin-Mining Land in Bangka - Savira, Savira; Nurtjahya, Eddy; Santi, Ratna (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2023)
Tin-mined land experiences drought, high light intensity, and temperature which is less supportive of plant growth. The study observed the anatomical responses of grasses leaves. This study aims to measure stomatal density, stomatal index, guard cell length, and guard cell width of three grass species that grow naturally in ex tin-mined land and in undisturbed land. Description method carried out based on the paradermal incision resulted in the wholemount method. The results showed each grass species has a different response to their different habitats. The stomatal density of Imperata cylindrica and Paspalum conjugatum collected from ex tin-mined land were higher than to those plants collected from undisturbed land, however the stomatal density in Scleria levis showed the opposite result. Stomatal index of all three species increases in ex tin-mined land were higher than in undistributed land. Guard cell lengths of I. cylindrica and P. conjugatum were smaller than those in undistributed land, but Scleria levis showed the opposite result. Guard cell width of I. cylindrica and S. levis were wider than those in undistributed land, but P. conjugatum showed the opposite result. These responses may reflect their adaptiveness to tin soils.